2017
DOI: 10.1016/j.envres.2017.05.033
|View full text |Cite
|
Sign up to set email alerts
|

Mercury concentrations in lean fish from the Western Mediterranean Sea: Dietary exposure and risk assessment in the population of the Balearic Islands

Abstract: The present study reports total mercury (THg) and methylmercury (MeHg) concentrations in 32 different lean fish species from the Western Mediterranean Sea, with a special focus on the Balearic Islands. The concentrations of THg ranged between 0.05mg/kg ww and 3.1mg/kg ww (mean 0.41mg/kg ww). A considerable number of the most frequently fish species consumed by the Spanish population exceed the maximum levels proposed by the European legislation when they originate from the Mediterranean Sea, such as dusky grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 28 publications
4
13
2
Order By: Relevance
“…Common dentex were found to have mean Total Hg concentrations of 0.78 μg/g ww which was lower than in a previous study in the western Mediterranean, 0.99 μg/g ww, and in the Egyptian coast, 1.1 μg/g ww (Llull et al, 2017).…”
Section: Mercurycontrasting
confidence: 77%
See 2 more Smart Citations
“…Common dentex were found to have mean Total Hg concentrations of 0.78 μg/g ww which was lower than in a previous study in the western Mediterranean, 0.99 μg/g ww, and in the Egyptian coast, 1.1 μg/g ww (Llull et al, 2017).…”
Section: Mercurycontrasting
confidence: 77%
“…The mean THg concentrations of the angler specimens analysed in the present study (1.9 μg/g ww) were much higher than those from the Italian coast (mean of 0.13 μg/g ww; Brambilla et al, 2013) and even previous studies near the Balearic Islands (0.74 μg/g ww; Llull et al, 2017).…”
Section: Mercurycontrasting
confidence: 74%
See 1 more Smart Citation
“…Primary dietary sources of cadmium in Spain are said to be cereals and fish [ 36 ], which was confirmed by our observations. Analogous results were observed for the dietary exposure of mercury—fish was the primary dietary source [ 36 , 64 , 65 , 66 , 67 , 68 ]. We observed a large contribution of cereals to total dietary lead exposure in two of the three considered heavy metals, together with fish and meat; this result supports previous investigations on the contribution of cereals to the dietary exposure of lead in Spain [ 69 ].…”
Section: Discussionsupporting
confidence: 64%
“…On the other hand, local studies suggested that predatory fish from the demersal zone and higher marine trophic level induced a greater mercury burden [ 5 , 29 ]. This is to be expected since bioaccumulation of mercury concentrations in fish would have happened at higher trophic levels [ 51 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%